Removal of Heavy Metal Copper (Cu) Ions from Wastewaters Using Various Bio-adsorbents - Khairunnisa Khairunnisa; Siti Rahmah; Rini Selly; Jasmidi Jasmidi; Hafni Indriati Nasution; Moondra Zubir (Indonesian Journal of Chemical Science and Technology (IJCST), 2022)
Biosorbent derived from agricultural waste as one of the widely used adsorbents has many applications in the environment to remove pollutants, one of which is heavy metal copper (Cu). In this paper, natural sources of agricultural waste materials have been reviewed and have potential as biosorbents for the absorption of heavy metal copper (Cu). The characteristics of the biosorbent that can be used for the absorption of heavy metal copper (Cu) depend on the surface area and pore structure made by the modified method. The biosorbent modification method depends on the precursor and the expected biosorbent characteristics. Natural biosorbents can be converted into modified biosorbents by chemical, physical, or physico-chemical modifications. Therefore, this paper aims to provide information about the absorption of adsorbents from agricultural wastes that have been reported for the absorption of heavy metal copper (Cu) in wastewater